Does tea extract supplementation benefit metabolic syndrome and obesity? A systematic review and meta-analysis. Issue 4 (April 2020) - Li, Xiumin; Wang, Wen; Hou, Liming; Wu, Huanghui; Wu, Yongjie; Xu, Rong; Xiao, Yuan; Wang, Xiaoming
Summary: Background: Given the global epidemic of obesity, numerous strategies have been employed in the management of metabolic syndrome (MS) in this population. A meta-analysis was designed in the present investigation to evaluate the benefits of tea extract (TE) supplementation in MS in obesity. Methods: We conducted searches of published literature in MEDLINE, PsycINFO, Scopus, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) databases from inception in 1985 to May 2017. Randomized controlled trials (RCTs) which studied TE consumption in obesity with MS were analyzed. Results were summarized using weighted mean differences (WMDs), standardized mean differences (SMDs) or odds ratio (OR) by suitable effect model. Results: Sixteen eligible randomized controlled trials, including 1090 subjects were identified. Benefits were demonstrated on reduction of Body Mass Index (BMI) (SMD,  −0.27; 95% CI,  −0.40 to −0.15, P  < 0.0001) and blood glucose (SMD,  −0.22; 95% CI,  −0.34 to −0.10, P  = 0.0003), and increasing high-density lipoprotein (HDL) (SMD, 0.18; 95% CI, 0.01 to 0.35, P  = 0.03). Limited benefits without significance were observed on blood pressure and other anthropometric, cholesterol, and biochemistry outcomes. All-cause adverse events were minimal (0.99; 95% CI: 0.55, 1.77, P  = 0.97). Conclusions: This meta-analysis suggests that consumption of TE supplementation in the obese with MS has beneficial effects on improvement of lipid and glucose metabolism, as well as in the facilitation of weight loss.